Labelling of the cytoplasmic domains of ovine rhodopsin with hydrophilic chemical probes. - Barclay, P L (1984)
The disposition of polypeptide chain of ovine rhodopsin in the photoreceptor disc membrane was investigated by using two hydrophilic reagents, 3,5-di-[125I]iodo-4-diazobenzenesulphonate [( 125I]DDISA) and [14C]succinic anhydride. Both reagents were used to modify rhodopsin in intact disc membranes under conditions where no loss of A500 occurred. Reaction of [125I]DDISA with rhodopsin approached completion after 30 min. Binding was saturated at a 75-fold molar excess of reagent, which gave binding ratios of up to 2 mol/mol of rhodopsin. Proteolysis of rhodopsin, using Staphylococcus aureus V8 proteinase, yielded two membrane-bound fragments, both of which contained bound radioactive probe. Subsequent CNBr cleavage of these fragments produced five radiolabelled peptides which corresponded to the C-terminal region and cytoplasmic loops of rhodopsin. Similar studies with [14C]-succinic anhydride also gave binding ratios of up to 2 mol/mol of rhodopsin. Sequencing of the [14C]succinylated peptides identified the location of the reactive sites as lysine residues 66, 67, 141, 245, 248, 311, 325 and 339 in the polypeptide chain. Non-permeability of both probes was demonstrated by the absence of any radioactivity associated with the intradiscal N-terminal glycopeptide. Sonication of membranes in the presence of [125I]DDISA led to the incorporation of label in this peptide.